A duopoly of transportation network companies and traditional radio-taxi dispatch service agencies - Heilker, Thorsten; Sieg, Gernot (European Journal of Transport and Infrastructure Research, 2018)
Transportation network companies commonly enter the market for taxi ride intermediation and alter the market outcome. Compared to cooperatively organized radio-taxi dispatch service agencies, transportation network companies run larger fleets and serve more customers with lower fares, when the fixed costs of the dispatch office are relatively small. The same holds for private dispatch firms, when the fixed costs of a taxicab are not too small. These results are shown in a two-stage duopoly of fare and fleet size competition with fare- and waiting-timedependent demand.